BLOOD LEVEL OF COLLAGEN BIOMARKERS AND SULFATED GLYCOSAMINOGLYCANS IN ACUTE TRANSMURAL MYOCARDIAL INFARCTION - A. V. Govorin; E. V. Ratsina; N. V. Fetisova; N. A. Sokolova (Российский кардиологический журнал, 2016)
Aim. To study dynamics of blood levels of carboxyterminal propeptide of I type procollagen (PICP), carboxyterminal telopeptide of type I collagen (CITP) and sulfated glycosaminoglycans (sGAG) in the dynamics, in patients with transmural transmural myocardial infarction (MI) complicated with aneurysm.Material and methods. Totally, 46 patients included with acute transmural anterior MI, who underwent the assessment of PICP, CITP and sGAG in dynamics.Results. On the 1st to 3rd days of MI without aneurysm there was increase of PICP up to 61,4 ng/mL, on 10-12th and 18-22nd days its level did not change significantly, remaining high. In aneurysm MI the level of PICP increased just from the 10-12th days and in lower grade — comparing to patients without aneurysm. Level of CITP in patients without aneurysm was comparable to controls during the entire study. Level of sGAG in non-aneurysm patients increased from 10-12th days, and in MI with aneurysm — did not differ from healthy persons during the entire study.Conclusion. Increase of CITP and lower PICP and sGAG in MI patients with aneurysm witnesses’ probable predominance of degradation processes of connective tissue over its synthesis.